2015
DOI: 10.1039/c5ra04118j
|View full text |Cite
|
Sign up to set email alerts
|

New insights in atmospheric acid-catalyzed gas phase hydrolysis of formaldehyde: a theoretical study

Abstract: A two-step mechanism of the gas phase hydrolysis of formaldehyde catalyzed by nitric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 76 publications
4
21
0
Order By: Relevance
“…For Channel RWM1, two kinds of reaction types can be taken (a) between H 2 O/Cl and HO 2 or (b) between H 2 O/HO 2 and Cl. When the H 2 O/Cl complex and HO 2 act as reactants, the reaction occurs in one elementary step, which is similar to the uncatalyzed reaction of HO 2 + Cl / HCl + O 2 above, the HCOOH-catalyzed hydrolysis of CH 3 CHO and HCHO, 41,70 as well as the HNO 3 and HCOOH-catalyzed hydrolysis of SO 3 . [71][72][73] The reaction starts with the formation of the pre-reactive complex IM_WM2, as described in Fig.…”
Section: Mechanism and Kinetics Of The H 2 O Catalyzed Ho 2 + CL / Hcmentioning
confidence: 93%
See 1 more Smart Citation
“…For Channel RWM1, two kinds of reaction types can be taken (a) between H 2 O/Cl and HO 2 or (b) between H 2 O/HO 2 and Cl. When the H 2 O/Cl complex and HO 2 act as reactants, the reaction occurs in one elementary step, which is similar to the uncatalyzed reaction of HO 2 + Cl / HCl + O 2 above, the HCOOH-catalyzed hydrolysis of CH 3 CHO and HCHO, 41,70 as well as the HNO 3 and HCOOH-catalyzed hydrolysis of SO 3 . [71][72][73] The reaction starts with the formation of the pre-reactive complex IM_WM2, as described in Fig.…”
Section: Mechanism and Kinetics Of The H 2 O Catalyzed Ho 2 + CL / Hcmentioning
confidence: 93%
“…The M06-2X functional is one of the best functionals with which to study noncovalent interactions 38,39 and has shown promising applications for estimating the thermochemistry and equilibrium structures for atmospheric reactions and molecular clusters. [40][41][42] At the M06-2X/6-311++G(2d,2p) level, the harmonic vibrational frequencies were calculated to verify the nature of the corresponding stationary points (minima or transition state) to provide the zero-point vibrational energy (ZPE) and to determine the thermodynamic contributions to the enthalpy and free energy. In addition, intrinsic reaction coordinate (IRC) [43][44][45] calculations were carried out to ensure that the transition states were connected to the desired reactants and products.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…and cis-H 2 SO 4 act as reactants, the reaction occurs in one elementary step, which is similar to the H 2 SO 4 -and HCOOH-catalyzed hydrolysis of CH 3 CHO and HCHO 29,74,75 as well as the HNO 3 -and HCOOH-catalyzed hydrolysis of SO 3 . 32,76,77 The reaction begins with complex IM_SA_1.…”
Section: Resultsmentioning
confidence: 83%
“…Thus, H 2 O 2 /HO complex can be neglected and it is not taken into account here. Such investigations have been studied in similar investigations, 52,[66][67][68][69][70] where the dimer between the two reactants has not been involved in X assisted reactions. Above step is followed since it is very necessary to rst identify the stable binary complexes of H 2 O 2 /X and HO/X.…”
Section: Reactantsmentioning
confidence: 99%